Quantifying the ecological and socioeconomic implications of a recovery/collapse of South Africa's West Coast rock lobster fishery - Eggers, Jessica Marguerite (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The West Coast rock lobster (WCRL) Jasus lalandii fishery is South Africa's third most valuable fishery, but the stock is currently at less than 2% of its pristine biomass. Scientists are warning that if no measures are taken, the WCRL could face commercial extinction. The necessary reductions in the global Total allowable Catch (TAC) seen in past years have had large economic implications for the WCRL value chain, but research into the socio-economic aspects of this fishery is limited. This study, therefore, aims to establish an overview of the economic revenue over the seasons 2016/17 "“ 2018/19 by exploring changes and trends in the net seasonal income (NSI) for the fishery, sectors within the fishery and different stakeholders. It also investigates the prospects for the sectors and different actors in this fishery over the seasons 2019/2020 - 2030/31 through analysis of the net present value (NPV) under three proposed global TAC management scenarios (global TAC of 640 tonnes, 1084 tonnes and 1280 tonnes). Data concerning costs and incomes as well as dynamics, mechanisms and concerns surrounding the fishery were collected from stakeholders in the different sectors through interviews and surveys. Further, official records from DEFF (catches, actors, vessels and quotas) and projections made by the Marine Resource Assessment (MARAM) team at the University of Cape Town (rates of recovery of the resource and future catches under the different TAC scenarios) were obtained and analysed. Cost and income data were summarised and models characterising the economic flows within the fishery were created. Calculations regarding the NSI and NPV were made using Monte Carlo simulations to account for the uncertainty surrounding many of the input variables. Results show that while the fishery as a whole made economic profits for the three seasons, the decreasing quotas in 2018/19 had a disproportionately negative impact on some of the representative individuals examined within the different sectors. The projections indicate that while each of the sectors as a whole would continue to make profits largely proportional to their allocation under the different TAC scenarios, many vessel owners in the fishery are likely to face economic losses or very marginal gains under the lower quota options, while the NPV for quota holders who outsource the catching of their quota are likely to be proportionally less affected by the changes in global TAC. This dynamic is important to consider for the future of this fishery. If the resource is to recover, and fishing activity is to continue equitably under the decreased quotas that the recovery of the biomass necessitates, the socio-economic context and the dynamics within which the fishers operate must be considered and studied more extensively and socio-economic consequences of a lower global TAC mitigated while improving the ecological status of the resource.
Keywords: Jasus lalandii -- South Africa; Lobster fisheries -- South Africa; Lobster fisheries Catch effort -- South Africa; Fishery management -- South Africa; Small-scale fisheries -- South Africa; Economics Sociological aspects; Value chain analysis